Penerapan Fungsi Manajemen Pada Gerakan Dakwah Di Pimpinan Wilayah Muhammadiyah Sumatera Utara - Manurung, Rahma Sari; Faridah (Fakultas Ushuluddin, Adab, dan Dakwah IAIN Parepare, 2024)
The purpose of this research is to understand how planning is applied in the da'wah movement and leadership of Muhammadiyah regions in Sumatra. The theory used is the management theory of Abdul Rofiq, with a qualitative approach to collecting data through interviews, observation, and documentation. The results showed that the movement of the North Sumatra Mumamadiyah regional leadership through Bil-Lisan, Bil-Hal and bi tadwin. as for Takhṭῑṭ (da'wah planning) PWM leadership is by determining which locations need da'wah handling, what kind of financing. And usually, the planning carried out needs deliberation with other members. Tanẓῑm (organizing/preparing da'wah) carried out by PDM can make da'wah activities run smoothly and in accordance with planning and neatly arranged through the membership structure. Tawjῑh (mobilisation/direction of da'wah) PWM said that the implementation of da'wah will be carried out after previous deliberations or da'wah planning. Before sending a da'i who will give da'wah, PDM ensures that there is already material and that the da'i has good communication skills and is good at adjusting to the culture of the community. Riqa‾bah (control and evaluation of da'wah) This da'wah supervision itself is carried out by PDM vertically in each region in accordance with the tanfidz of each Muhammadiyah region, each of which has a member as a supervisor during da'wah. If da'wah is not carried out and there are deviations, Muhammadiyah itself will not hesitate to reprimand, evaluate and expel members. Of course, in the delivery there are challenges and obstacles, but the leadership can provide solutions with the strategies that have been implemented. In conclusion, by implementing systematic and measurable planning, the da'wah movement under the leadership of Muhammadiyah North Sumatra can achieve its goals more effectively and efficiently, having a positive impact on the local community